BEFORE TEOTIHUACAN—ALTICA, EXCHANGE, INTERACTIONS, AND THE ORIGINS OF COMPLEX SOCIETY IN THE NORTHEAST BASIN OF MEXICO. Issue 2 (2019) - Nichols, Deborah L.; Stoner, Wesley D.
Abstract: For several decades, little research has been directed towards understanding the beginnings of complex society in the Teotihuacan Valley. Recent archaeological investigations at the Early–Middle Formative site of Altica provide a fresh perspective on dating the initial establishment of agricultural villages, early social and economic differentiation, and the development of intra-and interregional exchange networks to test comparative models of political economy.